PENERAPAN DISIPLIN GEREJA BERDASARKAN KITAB INJIL SEBAGAI PEDOMAN DALAM MELAYANI ORANG-ORANG YANG TERMAJILKAN - Manase Gulo (Manna Rafflesia, 2023)
The purpose of this study is to redefine the application of church discipline/strategies based on the Bible. The meaning of this discipline is to be a guideline for the church today when it finds its people falling into sin. The method used is qualitative research with an exemplary approach. The results of the study clearly state that the Bible has formulated a form of church discipline/tactics with the principles of serving, shepherding, and admonishing. The Bible says that the application of discipline has brought sinners to repentance. The Bible also states unequivocally that church discipline is not punishment but leads to the knowledge of Christ. Thus the church must be guided by Jesus' discipline pattern for sinners. The principle of Jesus' discipline is to seek and save the lost.